Experiences using a progestin-only pill in an over-the-counter environment in the United States: a cross-sectional survey. Issue 1 (21st October 2022) - Grindlay, Kate; Key, Katherine; Zuniga, Carmela; Wollum, Alexandra; Grossman, Daniel; Blanchard, Kelly
Abstract : Background: Efforts are underway to make a progestin-only pill (POP) over the counter (OTC) in the United States (US); however, little is known about POP user experiences, which could impact uptake and continuation. Methods: From January 2020–September 2021, we conducted a cross-sectional online survey with individuals who used OTC POPs in a US trial. We calculated descriptive statistics and Pearson chi-square and Fisher's exact tests to assess menstrual bleeding acceptability, how OTC POP experiences compared with prior contraceptive methods, and preferred ways to get answers to questions during OTC POP use. Results: Among 550 adult and 115 adolescent participants, 80% (n=531) felt their menstrual bleeding was acceptable. Participants reported a range of menstrual bleeding experiences compared with prior long-acting or hormonal methods used; 58% (n=84) said the POP bleeding was similar or better and 36% (n=53) said it was worse. Among participants who used contraception in the month prior to the trial, 77% (n=201) said their overall OTC POP experience was similar or better. Top benefits compared with prior methods included less worry about pregnancy, ease of access, fewer side effects, and greater decision-making power. Adults preferred to get answers about OTC POPs via webpage or app, whereas teens preferred asking pharmacists or other healthcare providers. Conclusions: Overall, OTC POP users in a trial setting found the menstrual bleeding acceptable and the method similar to or better than previous methods. POP labelling should provide clear messaging about bleeding changes users may experience.